Numerical research on lithium-ion battery thermal management utilizing a novel cobweb-like channel cooling plate exchanger - Zhao, Qian; Wu, Huawei; Wang, Zhaohui; Fan, Yiwei; Cheng, Wei (Frontiers in Energy Research, 2022)
As a key component of a pure electric vehicle, the battery in an overheated state will have a direct impact on battery life and vehicle safety. To promote battery heat dissipation, a novel cobweb-like type (C-type) channel cooling plate with asymmetric inlet and outlet is designed. The C-type channel cooling plate is numerically simulated in two coolant flow directions (Ifd and IIfd), using the computational fluid dynamics software STAR-CCM+, and compared to the conventional serpentine type (S-type) channel. Meanwhile, the effects of three structural parameters (channel diameter, spacing, and cooling plate thickness) on maximum temperature and temperature difference of the C-type cooling plate, and pressure drop are investigated. Based on this, the C-type channel is optimized by orthogonal test. The results show that the C-type with IIfd coolant flow direction has a better heat dissipation effect on the battery module than the C-type with Ifd and S-type under the same conditions, and the maximum temperature and temperature difference are respectively reduced by 0.2% and 17.8%, while the pressure drop is increased by 17.3%. In addition, increasing channel diameter can obtain good battery temperature distribution and smaller pressure drop, while the increase of cooling plate thickness and channel spacing has a greater effect on the battery temperature difference compared to the change of maximum temperature. Finally, the results of the orthogonal tests show that the cooling effect is best when the diameter of the cobweb-like channel cooling plate is 7 mm, the thickness of the cooling plate is 12 mm, and the channel spacing is 16 mm, and the maximum temperature and temperature difference are reduced by 0.7% and 6.8%, respectively, and the pressure drop is reduced by 37.6% compared to the initial cobweb-like channel scheme. This offers a fresh perspective on cooling plate channel design in liquid-cooled battery thermal management.